Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature and preparation method of Mg-Sc magnesium alloy

By preparing Mg-35wt%Sc alloy and using vacuum smelting, homogenizing solid solution treatment and hot extrusion treatment, the problem of insufficient mechanical properties of existing Mg-Sc alloys is solved, and its mechanical properties are significantly improved, which is suitable for the field of mechanical structures.

CN119663083AActive Publication Date: 2025-03-21CHINA JILIANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411912544.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The comprehensive mechanical properties of existing Mg-Sc alloys are not excellent enough, and their ultimate tensile strength and elongation are low, which limits their application in the field of mechanical structures.

Method used

By preparing Mg-35wt%Sc alloy, vacuum smelting, homogenizing solution treatment and hot extrusion treatment are used, combined with heat treatment and cooling treatment, the mechanical properties of the alloy are improved.

Benefits of technology

The tensile yield strength, ultimate tensile strength and elongation of Mg-35wt%Sc alloy have been significantly improved, and the performance has been greatly improved, which is suitable for the field of mechanical structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663083A_ABST
    Figure CN119663083A_ABST
Patent Text Reader

Abstract

The invention discloses a room-temperature high-strength and medium-plasticity Mg-Sc magnesium alloy and a preparation method thereof, and belongs to the technical field of magnesium alloy materials. Pure Sc and an Mg-30wt% Sc alloy are used as raw materials to be proportioned into an Mg-35wt% Sc alloy, the Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature is obtained through vacuum melting, homogenization solution treatment, hot extrusion treatment, heat treatment and different cooling modes, and the problem that in the prior art, the comprehensive mechanical property of the Mg-Sc alloy is not excellent enough is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloy materials, and in particular relates to a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature and a preparation method thereof. Background Art

[0002] It is generally believed that magnesium and its alloys are promising candidates for structural materials in the fields of medicine, automobiles, and aviation due to their good biocompatibility, high specific strength, and light weight. However, due to the anisotropy of the hexagonal close-packed (hcp) structure, traditional magnesium alloys (such as Mg-Ca, Mg-Zn, and Mg-Al series) with hcp structure (α phase) usually show poor ductility during room temperature deformation. People have tried to introduce the isotropic body-centered cubic (bcc) structure (β phase) into traditional magnesium alloys to fundamentally improve their ductility. It is well known that since metals with bcc structure have more slip systems than metals with hcp structure, isotropic β-type Mg-Li alloys with bcc structure can achieve excellent plastic deformation ability. Therefore, one of the practical methods to improve the ductility of magnesium alloys is to transform the phase structure from hcp structure to bcc structure.

[0003] Scandium (Sc) is widely used as an alloying element for aluminum alloys in aerospace, automotive and other fields. For example, it is beneficial to grain refinement, which can improve the mechanical properties and corrosion resistance of magnesium alloys. Regarding mechanical properties, it is well known that the maximum solid solubility of scandium in Mg is 24.5wt%. Therefore, the mechanical properties of magnesium alloys can be improved by the solid solution strengthening effect. Most importantly, Sc is the only rare earth element that can transform the Mg matrix from the hcp structure to the bcc structure. It is worth noting that the superelastic behavior of 4.4% was observed in the β-type Mg-20.5at%Sc alloy reported by Ogawa et al. at -150 °C. In the β-type Mg-18.3at%Sc alloy, a significant shape memory effect was observed during heating to room temperature. They attributed the shape memory effect and superelasticity to the thermoelastic martensitic phase transformation between the α" with orthorhombic structure and the β phase with bcc structure in the β-type Mg-Sc alloy. These significant discoveries have triggered great interest in Mg-Sc alloys with high Sc content.

[0004] In the field of Mg-Sc alloy research, in "The Effect of Sc on Mechanical Properties and Corrosion Resistance of Pure Magnesium" (Zhang Manyu, Shanghai Jiaotong University, 2018.DOI:10.27307 / d.cnki.gsjtu.2018.003459), a series of binary Mg-Sc alloys (Mg-2wt%Sc, Mg-5wt%Sc, Mg-10wt%Sc and Mg-15wt%Sc) were disclosed. Among them, the comprehensive mechanical properties of Mg-5wt%Sc alloy are the worst, with the ultimate tensile strength (UTS) and elongation of only about 120MPa and 7.6%, respectively; while the UTS and elongation of Mg-10wt%Sc alloy with the best comprehensive mechanical properties are only about 143MPa and 10.3%, respectively, which greatly limits the direct application of Mg-Sc alloy as mechanical structural materials. In "Effect of Y on Mechanical and Corrosion Properties of Mg-Sc Binary Alloys" (Xu Xinmei, Shanghai Jiao Tong University, 2019. DOI: 10.27307 / d.cnki.gsjtu.2019.002983), the room temperature tensile mechanical properties of Mg-5Sc, Mg-5Sc-0.5Y, Mg-5Sc-1Y, Mg-5Sc-2Y, Mg-5Sc-3Y and Mg-5Sc-3.5Y (wt%) alloys are disclosed. The tensile yield strength (YS) and elongation of the Mg-5Sc alloy without Y addition are only about 70MPa and 9.0%, respectively; the YS and elongation of the Mg-5Sc-3Y alloy with the best comprehensive mechanical properties are only about 107MPa and 15.5%, respectively, which also limits the direct application of Mg-Sc alloys as mechanical structural materials in industry. The Chinese patent with application number 202311034348.8 discusses the mechanical properties of a series of medical Mg-Sc magnesium alloys (Mg-0.5wt%Sc, Mg-1wt%Sc, Mg-3wt%Sc and Mg-5wt%Sc). Among them, the UTS of the Mg-0.5wt%Sc alloy with the worst mechanical properties is only 198MPa, while the UTS of the Mg-3wt%Sc alloy with the best mechanical properties is only 245MPa. Although both types of alloys have an elongation of more than 37.2%, their comprehensive mechanical properties are still relatively low.In the field of non-Mg-Sc alloy research, the room temperature tensile mechanical properties of AZ31 alloy were reported in "Microstructure and mechanical properties of wire and arc additive manufactured AZ31 magnesium alloy using cold metal transfer process" (X. Yang, J. Liu, Z. Wang, X. Lin, F. Liu, W. Huang, E. Liang, Mater. Sci. Eng. A 774 (2020) 138942). Among them, the UTS and elongation of AZ31 with the best mechanical properties were only about 210.5 MPa and 10.55%, respectively. In "Thermal stability, grain growth kinetics, mechanical properties, and bio-corrosion resistance of pure Mg, ZK30, and ZEK300 alloys: A comparative study" (Z.Savaedi, H.Mirzadeh, R.M.Aghdam, R.Mahmudi, Mater. Today Commun. 33 (2022) 104825), the mechanical properties of ZK30 series magnesium alloys were studied. The study showed that the UTS and elongation of ZK30 magnesium alloy were only about 260.1 MPa and 10.60%, respectively. At the same time, the mechanical properties of ZK60 series magnesium alloys were discussed in "Evolution of the microstructure, texture and mechanical properties of ZK60 alloy during processing by rotating shear extrusion" (L. Yan, Z. Zhang, G. Li, Y. Xue, J. Xu, J. Alloy. Compd. 877 (2021) 160229). The study showed that the UTS and elongation of ZK60 magnesium alloy were only about 278.0 MPa and 10.00%, respectively. Obviously, these magnesium alloys still have relatively low comprehensive mechanical properties, so it is necessary to further improve the comprehensive mechanical properties of magnesium alloys such as Mg-Sc to broaden the application of magnesium alloys such as Mg-Sc as mechanical structures. Summary of the invention

[0005] In view of the above technical problems, the present invention proposes a room temperature high-strength and medium-plastic Mg-Sc magnesium alloy and a preparation method thereof, which solves the problem that the comprehensive mechanical properties of Mg-Sc alloy in the prior art are not excellent enough.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the purposes of the present invention is to provide a method for preparing a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature, comprising the following steps:

[0008] Pure Sc and Mg-30wt%Sc alloy are used as raw materials to prepare a Mg-35wt%Sc alloy mixture;

[0009] The Mg-35wt%Sc alloy mixture is subjected to vacuum melting and homogenization solution treatment in sequence, and then hot extruded at 510°C for 30 minutes, and air-cooled to obtain a Mg-35wt%Sc alloy rod sample with a diameter of 14 mm;

[0010] The Mg-35wt% Sc alloy rod specimens were cut into specimens with a thickness of 2 mm, and then the specimens were polished with 100#, 500#, 1000# and 2000# sandpapers in sequence until the alloy surface was bright, and then heat treated at 540°C for 30 minutes. The heat-treated specimens were cooled to obtain a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature.

[0011] The present invention improves the comprehensive mechanical properties of the existing magnesium alloy by adding alloying rare earth element Sc, machining and changing the heat treatment process. The maximum solid solubility of Sc in α-Mg is relatively high (about 24.5wt%), and the introduction of Sc atoms into the Mg matrix will cause the Mg lattice to deform, increasing the resistance to dislocation and slip during tensile deformation, so the comprehensive mechanical properties of the magnesium alloy can be improved by solid solution strengthening.

[0012] Furthermore, the pure Sc and Mg-30wt% Sc alloys need to be pretreated before use. The specific treatment method is: polishing with 100#, 500#, 1000# and 2000# sandpapers in sequence until the alloy surface is bright, and then cleaning with anhydrous ethanol and drying.

[0013] Furthermore, the specific steps of vacuum melting include: using a vacuum induction melting furnace for melting, when the vacuum degree in the furnace is drawn to 5.0×10 -3 After reaching Pa, 0.05MPa of pure argon gas was filled into the furnace, and the power was turned on. After the raw materials were completely melted, the Mg-35wt%Sc melt was kept boiling for 3min, and then kept at a current of 10A for 10min. The obtained magnesium alloy was cooled to room temperature with the furnace, and the cast Mg-35wt%Sc alloy was taken out.

[0014] Furthermore, the vacuum melting operation is repeated 3 times.

[0015] Furthermore, the extrusion ratio during the hot extrusion process is 11.6.

[0016] Furthermore, the specific steps of the homogenization solution treatment include: keeping the cast Mg-35wt%Sc alloy obtained by vacuum melting at 610°C for 12 hours, water quenching at room temperature, and polishing the obtained sample with 100#, 500#, 1000# and 2000# sandpaper in turn until the surface of the alloy is bright to obtain a Mg-35wt%Sc alloy.

[0017] Furthermore, the cooling treatment method includes one of furnace cooling, air cooling and room temperature water cooling.

[0018] The second object of the present invention is to provide a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature prepared by the above preparation method.

[0019] Furthermore, the room temperature high strength and medium plasticity Mg—Sc magnesium alloy comprises the following components, in terms of mass percentage: 35.0wt% of Sc, the content of inevitable impurities ≤0.02wt% and the balance Mg.

[0020] The third object of the present invention is to provide a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature for use in the field of mechanical structures.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects:

[0022] The Mg-35wt%Sc alloy prepared by the present invention has a tensile yield strength (YS) of about 263.0-276.0MPa, an ultimate tensile strength (UTS) of about 312.0-322.0MPa, and an elongation of about 7.2-15.6%. Compared with the existing magnesium alloys, the comprehensive mechanical properties have been greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0024] Figure 1 XRD patterns of Mg-35wt%Sc alloys prepared in Example 1(a), Example 2(b), and Example 3(c);

[0025] Figure 2SEM images of Mg-35wt%Sc alloys prepared in Example 1(a), Example 2(b), and Example 3(c);

[0026] Figure 3 EBSD images of Mg-35wt%Sc alloys prepared in Example 1 (FC), Example 2 (AC), and Example 3 (WQ); wherein (a, d, g) are phase images of superimposed α phase (green area) and β phase (red area); (b, e, h) α and (c, f, i) are IPF images of β phase;

[0027] Figure 4 The grain size diagrams of the Mg-35wt%Sc alloys prepared in Example 1 (FC), Example 2 (AC), and Example 3 (WQ); wherein (a, d, g) are grain size diagrams of α and β phases; (b, e, h) are statistical diagrams of the grain size of the α phase; (c, f, i) are statistical diagrams of the grain size of the β phase;

[0028] Figure 5 Room temperature tensile stress-strain curves (a) and mechanical data (b) of the Mg-35wt%Sc alloys prepared in Example 1 (FC), Example 2 (AC), and Example 3 (WQ). DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] The present invention provides a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature. The magnesium alloy comprises the following components in terms of mass percentage (wt%): Sc: 35.0wt%, the content of inevitable impurities ≤ 0.02wt%, and the balance Mg. The specific preparation method comprises the following steps:

[0035] (1) Ingredients: Pure Sc (>99.99wt%, Hunan Rare Earth Metal Materials Research Institute, China) and Mg-30wt% Sc alloy (>99.00wt%, Hunan Rare Earth Metal Materials Research Institute, China) are used as raw materials. The required raw materials are cut by wire cutting machine, and polished with 100#, 500#, 1000# and 2000# sandpapers in turn until the alloy surface is bright to remove the stains and oxide layer on the raw material surface, and washed with anhydrous ethanol (analytical pure 99.7%, Tianjin Fengchuan, the same below), and then low-temperature dried to prepare Mg-35wt% Sc alloy mixture according to the component ratio.

[0036] (2) Melting: Place the raw materials into a BN (boron nitride) crucible and then into a melting furnace, and then use a vacuum induction melting furnace for melting. Use a mechanical pump to evacuate the furnace body. When the vacuum degree in the furnace reaches 5.0×10 -1 After that, the vacuum degree in the cavity was pumped to 5.0×10 -3 Pa, and then fill the furnace with 0.05MPa pure argon as a protective gas, turn on the heating power of the induction melting instrument, slowly increase the current of the induction melting instrument, and keep the magnesium melt boiling for 3 minutes after the raw materials are completely melted; keep it at a current of 10A for 10 minutes to ensure that the raw materials are evenly mixed; after the smelting is completed, turn off the power of the instrument, wait for the magnesium alloy to cool to room temperature with the furnace, then open the furnace door and take out the cast Mg-35wt%Sc alloy ingot; put the cast Mg-35wt%Sc alloy ingot into the induction melting furnace again and smelt it in the same way for 3 times to make the composition uniform.

[0037] (3) Homogenization solution treatment: The cast Mg-35wt%Sc alloy ingot obtained in step (2) is subjected to homogenization solution treatment in an integrated muffle furnace. When the temperature in the muffle furnace rises to 610°C, the cast Mg-35wt%Sc alloy ingot is placed in the muffle furnace for 12 hours, and then the Mg-35wt%Sc alloy is placed in room temperature distilled water (about 25°C) for water quenching. The obtained Mg-35wt%Sc alloy is polished with 100#, 500#, 1000# and 2000# sandpaper in turn until the alloy surface is bright, so as to remove stains and oxide layer on the surface of the raw material.

[0038] (4) Machining: The Mg-35wt%Sc alloy obtained in step (3) is subjected to hot extrusion treatment. A hot extrusion test is performed using an 80T hydraulic press, an extrusion die (extrusion ratio of 11.6), a copper heating coil and a temperature controller. The Mg-35wt%Sc alloy after homogenization and solution treatment is first processed into a size suitable for placement in the sleeve, and graphite is applied to the magnesium alloy sample and the extrusion die. The extrusion die, pure copper heating coil and temperature controller are then installed on the hydraulic press. The magnesium alloy sample is placed in the extrusion die, and the heating temperature is set to 510°C. The sample is extruded at this temperature for 30 minutes to obtain a Mg-35wt%Sc alloy rod sample with a diameter of 14 mm, and the rod sample is then air-cooled.

[0039] (5) Heat treatment and quenching process: The Mg-35wt%Sc alloy rod sample obtained in step (4) is cut into samples with a thickness of 2 mm by a wire cutting machine, and these samples are polished with 100#, 500#, 1000# and 2000# sandpaper in turn until the alloy surface is bright to remove the stains and oxide layer on the raw material surface, and the sample with a thickness of 2 mm is heat treated at 540°C × 30 min in a muffle furnace, and the heat-treated samples are subjected to different heat treatment cooling methods to obtain Mg-35wt%Sc alloys with different microstructures, and these alloys are polished with 100#, 500#, 1000#, 2000# and 3000# sandpaper in turn until the alloy surface is bright to obtain Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature.

[0040] The heat treatment cooling method includes one of furnace cooling (FC), air cooling (AC) and room temperature water cooling (WQ).

[0041] The "room temperature" mentioned in the present invention refers to 25±2°C unless otherwise specified.

[0042] The technical solution of the present invention is further illustrated by the following embodiments.

[0043] Example 1

[0044] A Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature, wherein the magnesium alloy comprises the following components in terms of weight percentage (wt%): Sc: 35.0wt%, the content of inevitable impurities ≤ 0.02wt%, and the balance Mg. The specific preparation method comprises the following steps:

[0045] (1) Ingredients: The raw materials of pure Sc and Mg-30wt%Sc alloy were cut by wire cutting machine, and polished with 100#, 500#, 1000# and 2000# sandpapers in sequence until the surface of the alloy was bright, and then washed with anhydrous ethanol, dried and mixed into Mg-35wt%Sc alloy mixture according to the component ratio;

[0046] (2) Melting: The raw materials prepared in step (1) are placed in a BN crucible and then in a melting furnace. The furnace is evacuated with a mechanical pump. When the vacuum degree in the furnace reaches 5.0×10 -1 After that, the vacuum degree in the cavity was pumped to 5.0×10 -3 Pa, then fill the furnace with 0.05MPa pure argon as a protective gas, turn on the heating power of the induction melting instrument, slowly increase the current of the induction melting instrument, and keep the magnesium melt boiling for 3 minutes after the raw materials are completely melted; keep it at a current of 10A for 10 minutes; after the smelting is completed, turn off the power of the instrument, wait for the magnesium alloy to cool to room temperature with the furnace, then open the furnace door and take out the cast Mg-35wt%Sc alloy ingot; put the cast Mg-35wt%Sc alloy ingot into the induction melting furnace again and smelt it in the same way for 3 times;

[0047] (3) homogenization solution treatment: when the temperature in the muffle furnace rises to 610° C., the cast Mg-35wt%Sc alloy ingot obtained in step (2) is placed in the muffle furnace for 12 hours, and then the Mg-35wt%Sc alloy is placed in room temperature distilled water (about 25° C.) for water quenching. The obtained Mg-35wt%Sc alloy is polished with 100#, 500#, 1000# and 2000# sandpaper in sequence until the alloy surface is bright;

[0048] (4) Machining: A hot extrusion test was performed using an 80T hydraulic press, an extrusion die (extrusion ratio of 11.6), a copper heating coil and a temperature controller. The Mg-35wt%Sc alloy obtained in step (3) was first processed into a size suitable for being placed in a sleeve. Graphite was then applied to the magnesium alloy sample and the extrusion die. The extrusion die, the pure copper heating coil and the temperature controller were then installed on the hydraulic press. The magnesium alloy sample was placed in the extrusion die. The heating temperature was set to 510°C. The sample was extruded at this temperature for 30 min to obtain a Mg-35wt%Sc alloy rod sample with a diameter of 14 mm. The rod sample was then air-cooled.

[0049] (5) Heat treatment and quenching process: The Mg-35wt%Sc alloy rod sample obtained in step (4) is cut into a sample with a thickness of 2 mm by a wire cutting machine, and then polished with 100#, 500#, 1000# and 2000# sandpapers in sequence until the alloy surface is bright, and then the sample with a thickness of 2 mm is heat treated at 540°C × 30 min in a muffle furnace, and the heat-treated sample is cooled by furnace cooling (FC), and finally polished with 100#, 500#, 1000#, 2000# and 3000# sandpapers in sequence until the alloy surface is bright, to obtain a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature.

[0050] Example 2

[0051] The same as Example 1, except that in step (5), the method of cooling the sample after heat treatment is replaced by air cooling (AC).

[0052] Example 3

[0053] The same as Example 1, except that in step (5), the method of cooling the sample after heat treatment is replaced by room temperature water cooling (WQ).

[0054] Performance Testing

[0055] The Mg-35wt%Sc alloy prepared in Example 1-3 was analyzed by X-ray diffractometer. The results are as follows: Figure 1 shown. Figure 1 The results show that the Mg-35wt%Sc alloys prepared in Examples 1-3 contain only α phase and β phase, and the β phase in Example 1 (FC) is the least, the β phase in Example 2 (AC) is the second, and the β phase in Example 3 (WQ) is the most. According to the position of the diffraction peak, the lattice constant of the α phase is obtained: a α =b α =0.328nm, c α =0.523nm, lattice constant of β phase: a β =b β =c β =0.361nm.

[0056] The Mg-35wt%Sc alloy prepared in Example 1-3 was observed by scanning electron microscope. Figure 2 shown. Figure 2 The results show that in the Mg-35wt%Sc alloys prepared in Example 1 (FC), Example 2 (AC) and Example 3 (WQ), the β phase presents an irregular morphology distribution, and the β phase in all samples is concentrated at the α phase boundary. With the increase of the heat treatment cooling rate, the content and size of the β phase in the sample gradually increase.

[0057] The Mg-35wt%Sc alloy prepared in Example 1-3 was observed by electron backscatter diffraction (EBSD). The results are as follows: Figure 3 shown. Figure 3 The results show that the β phase in the Mg-35wt% Sc alloy prepared in Examples 1-3 is mainly distributed at the phase boundary of the α phase, and the volume fractions of the β phase in the samples of Example 1 (FC), Example 2 (AC) and Example 3 (WQ) are 1.3%, 4.9% and 12.8%, respectively.

[0058] The Mg-35wt%Sc alloy prepared in Examples 1-3 was subjected to grain size analysis of the α and β phases in the sample based on EBSD data. The results are as follows: Figure 4 shown. Figure 4 The results show that the average grain sizes of α phase and β phase in the Mg-35wt%Sc alloys prepared in Examples 1-3 vary with the cooling rate during heat treatment. The average grain sizes of α phase in the samples of Example 1 (FC), Example 2 (AC) and Example 3 (WQ) are approximately 33.3μm, 32.9μm and 31.6μm, respectively; while the average grain sizes of β phase in the samples of Example 1 (FC), Example 2 (AC) and Example 3 (WQ) are approximately 2.2μm, 4.1μm and 9.5μm, respectively.

[0059] The room temperature tensile mechanical properties of the Mg-35wt%Sc alloys prepared in Examples 1-3 were tested. The room temperature tensile stress-strain curves and mechanical data are shown in Figure 5 shown. Figure 5 The results show that the YS of the Mg-35wt% Sc alloy prepared in Example 1 (FC) is 263.0MPa, UTS is 322.0MPa, and the elongation is 15.6%; the YS of the Mg-35wt% Sc alloy prepared in Example 2 (AC) is 263.3MPa, UTS is 312.0MPa, and the elongation is 11.7%; the YS of the Mg-35wt% Sc alloy prepared in Example 3 (WQ) is 276.0MPa, UTS is 313.0MPa, and the elongation is 7.2%.

[0060] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature, characterized in that: The following steps are involved: Pure Sc and Mg-30wt%Sc alloy are used as raw materials to prepare a Mg-35wt%Sc alloy mixture; The Mg-35wt%Sc alloy mixture is subjected to vacuum melting and homogenization solution treatment in sequence, and then hot extruded at 510°C for 30 minutes, and air-cooled to obtain a Mg-35wt%Sc alloy rod sample with a diameter of 14 mm; The Mg-35wt% Sc alloy rod specimens were cut into specimens with a thickness of 2 mm, and then the specimens were polished with 100#, 500#, 1000# and 2000# sandpapers in sequence until the alloy surface was bright, and then heat treated at 540°C for 30 minutes. The heat-treated specimens were cooled to obtain a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature.

2. The method for preparing a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature according to claim 1, characterized in that: The pure Sc and Mg-30wt% Sc alloys need to be pretreated before use. The specific treatment method is: polishing with 100#, 500#, 1000# and 2000# sandpaper in sequence until the alloy surface is bright, and then cleaning with anhydrous ethanol and drying.

3. The method for preparing a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature according to claim 1, characterized in that: The specific steps of vacuum melting include: using a vacuum induction melting furnace for melting, when the vacuum degree in the furnace is drawn to 5.0×10 -3 After reaching Pa, 0.05MPa of pure argon gas was filled into the furnace, and the power was turned on. After the raw materials were completely melted, the Mg-35wt%Sc melt was kept boiling for 3min, and then kept at a current of 10A for 10min. The obtained magnesium alloy was cooled to room temperature with the furnace, and the cast Mg-35wt%Sc alloy was taken out.

4. The method for preparing a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature according to claim 1, characterized in that: The vacuum melting operation was repeated 3 times.

5. The method for preparing a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature according to claim 1, characterized in that: The extrusion ratio during the hot extrusion process was 11.

6.

6. The method for preparing a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature according to claim 1, characterized in that: The specific steps of the homogenization solution treatment include: keeping the cast Mg-35wt%Sc alloy obtained by vacuum melting at 610°C for 12 hours, water quenching at room temperature, and polishing the obtained sample with 100#, 500#, 1000# and 2000# sandpaper in sequence until the alloy surface is bright to obtain the Mg-35wt%Sc alloy.

7. The method for preparing a Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature according to claim 1, characterized in that: The cooling treatment method includes one of furnace cooling, air cooling and room temperature water cooling.

8. A Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature prepared by the preparation method according to any one of claims 1 to 7.

9. The Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature according to claim 8, characterized in that: The invention comprises the following components in terms of mass percentage: 35.0wt% of Sc, the content of inevitable impurities is ≤0.02wt% and the balance is Mg.

10. Use of the Mg-Sc magnesium alloy with high strength and medium plasticity at room temperature as claimed in any one of claims 8 to 9 in the field of mechanical structures.

Citation Information

Patent Citations

  • High-toughness single-phase solid solution magnesium rare earth-based alloy at room temperature and its preparation method

    CN102277521A

  • Preparation method for magnesium alloy profile material for automobile oil tank

    CN106591658A

  • Zinc alloy for zipper and preparing method of zinc alloy

    CN107385279A

  • Mg-Sc magnesium alloy with high corrosion resistance and preparation method thereof

    CN117127074A

  • Biphase heterostructure and TRIP effect combined strongly-plasticized magnesium alloy and preparation method thereof

    CN118792561A